Clinical, etiological and imaging profile of posterior reversible encephalopathy syndrome: A prospective and follow-up study - Saurabh Bansal; Ramandeep Bansal; Manoj Kumar Goyal; Aastha Takkar; Ramandeep Singh; Paramjeet Singh; Vivek Lal (Annals of Indian Academy of Neurology, 2020)
Background: Although first described more than two decades ago, posterior reversible encephalopathy syndrome (PRES) continues to be enigmatic. We prospectively followed consecutive patients of PRES both clinically and radiologically for a better understanding of natural history, symptomatology, and prognosis of this not so uncommon entity. Patients and Methods: The current study included 22 consecutive patients of PRES who were followed both clinically as well as radiologically at a tertiary care institute in Northern India from December 2014 to June 2016. Results: Mean age was 30.68 ± 12.68 years. The most common symptoms included altered sensorium (77.3%), headache (72.7%), seizures (63.6%), vomiting (36.4%), and visual disturbances (22.7%). About 94.5% of patients had parieto-occipital signal changes on neuroimaging. Magnetic resonance imaging (MRI) (n = 20) revealed involvement of sites considered atypical for PRES in 95% (frontal [55%], temporal [40%], cerebellum [40%], basal ganglia [15%], deep white matter [10%] and brainstem [10%]). Diffusion restriction, haemorrhage, and contrast enhancement were seen in 30%, 22.2%, and 25% of patients. At 3 months follow-up, modified Rankin scale was 0 in 19 patients and 1 in 1 patient. Two (9.1%) patients died. Eight (36.4%) patients had eclampsia, 5 (22.7%) each had chronic kidney disease and essential hypertension whereas 2 (9.1%) each had immune-mediated disorders and drug-induced PRES. None of the clinical or imaging features predicted outcome in PRES. Conclusion: Atypical MRI presentations of PRES are common, and there is a need to keep a strong index of suspicion for the diagnosis of PRES. The prognosis of PRES is good, and most cases show excellent recovery, particularly if underlying etiology can be treated satisfactorily.